Level of Strength, Arm Strength, and Breaststroke Swimming Ability in Students of SMP Negeri 40 Makassar - Saleh, Muhammad Syahrul (Sains Global Institut, Indonesia, 2024)
This study aims to determine the level of leg strength, arm strength, and the relationship with breaststroke swimming ability in students of SMP Negeri 40 Makassar. This study is descriptive. The population and sample amounted to 20 people. The data analysis technique used the SPSS version 22 program at a significance level of α = 0.05 (95%). The conclusion of the data obtained from the leg strength measurement test obtained from the half squat jump for 30 seconds is a very good classification (1) person (5%), good classification (9) people (45%), moderate classification (6) people (30%), poor classification as many as (2) people (10%), and very poor classification as many as (2) 0 people (10%). Thus, it can be concluded that the results of the half squat jump test for 30 seconds obtained in students of SMP Negeri 40 Makassar can be categorized as moderate with an average result of 38 (descriptive data results). The conclusion of the data obtained from the arm strength measurement test obtained from push-ups for 30 seconds is a very good classification of as many as (0) people (0%). Good classification of as many as (0) people (0%), Moderate classification of (12) people (60%), Less classification of as many as (5) people (25%), and Very Less classification of as many as (3) people (15%). Thus, it can be concluded that the push-up test results obtained by students of SMP Negeri 40 Makassar can be categorized as less with an average result of 31 (descriptive data results). And in the 50-meter breaststroke swimming ability test, the classification is very good as many as (0) people (0%). Good classification of as many as (2) people (10%), Moderate classification of (7) people (35%), Less classification of as many as (6) people (30%), and Very Less classification of as many as (5) people (25%). Thus, it can be concluded that the results of the 50-meter breaststroke swimming test obtained by students of SMP Negeri 40 Makassar can be categorized as less with an average result of 1.36 minutes (descriptive data results).